Can street-level bureaucrats be nudged to increase effectiveness in welfare policy?. (1st January 2021) - Visintin, Emilio Paolo; Bonvin, Jean-Michel; Varone, Frédéric; Butera, Fabrizio; Lovey, Max; Rosenstein, Emilie
Abstract : This article investigates whether street-level bureaucrats can be incentivised to process information in ways that lead to more effective implementation decisions. It draws on the literatures on behavioural public policy (BPP) and street-level bureaucracy to analyse how civil servants implement disability insurance policy in Switzerland. We conducted a field experiment to assess whether a thought-provoking nudge improves the decisional effectiveness of street-level bureaucrats (SLBs). SLBs were assigned to either a 'business-as-usual' control condition, or to an experimental condition, where they were called to pay attention to vulnerability processes along the beneficiaries' life course when making decisions. While we did not find that the thought-provoking nudge directly improved effectiveness, we found that it increased beneficiaries' humanisation. In particular, there was some evidence for indirect positive effects of the thought-provoking nudge on effectiveness via humanisation. These findings encourage BPP researchers to consider additional dimensions such as humanisation to nudge SLBs into processing information in better ways.